Sistem maklumat memori organisasi di FSKSM - Hamidi, Saidatul Rahah (2006)
Data, information and knowledge have increased within organization across time. Then it becomes wasted memories because of retired staffs, died or removes to another place. This could give great impact when intellectual capital did not being used wisely for future purposes. Unit of academic management contains the main critical memories for Faculty of Computer Science and Information System. It needs to be managed accordingly. Otherwise, time, money and energy are wasted when the same work, research and finding information needed have to be done repeatedly. The lost may affect towards the quality of faculty curriculum. Therefore, the purpose of this thesis is to implement information technology in organizational memory of FSKSM through organizational memory information system (OMIS). A metadata will be build based on approved curriculum as a memories repository. This system is proposed as a prototype to be implemented for the whole module of FSKSM in order to protect their intellectual capital and optimizing the efficiency by managing organizational memory.